Práticas de Modelagem Matemática e o despertar para a consciência crítica de estudantes do Ensino Fundamental - Duarte , Adriéli Aline (2022)
In this research, we seek to investigate how Mathematical Modeling, assumed as a pedagocical practice, and from the perspective of Critical Mathematics Education, contributes to the awakening of critical awareness of students in the early years of Elementary School. In other words, we intend to investigate manifestations of students' awareness as they deal with problems evoked by real situations, in order to interrrogate: what contributions Mathematical Modeling activities, in the perspective of Critical Mathematics Education can bring to manifestations of Initial Years Elementary School's students critical awareness? The production and data collection were carried out in a municipal school in the west of Paraná and the research subject were students in a 5th grade Elementary School classroom in which a researcher worked as regent teacher. Guided by the research question, we made a local analysis, considering the specific episodes of the student’s dialogues undertaken during each activity, and a global analysis, in which all the set of episodes was analyzed. We take awareness according to the precepts of Freire (2020a), for whom the development of a continuous process of awareness, by going through different levels of apprehension of reality, enables effective awareness, a condition to act in favor of changes facing the reality experienced. In the face ot the previous results, we infer that Mathematical Modeling practices, initially, encouraged students to read the world, to read their reality, in a different way from what they were used to, that is, through a critical len, which questions, seeks to have knowledge, to then understand the problem that presents itself and, finally, to solve it through Mathematics.